Pengaruh Keterlibatan Penyuluh Pertanian dan Budaya Organisasional terhadap Kinerja Penyuluh Pertanian dengan Kohesivitas sebagai Mediasi pada Dinas Pertanian dan Ketahanan Pangan di Daerah Istimewa Yogyakarta - Daris Firman Ardiansyah; Purbudi Wahyuni; Sri Dwi Ari Ambarwati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of work involvement, organizational culture, and cohesiveness on the performance of agricultural extension workers at the Department of Agriculture and Food Security of Yogyakarta Special Region. The approach used is quantitative, the population is 263 civil servant extension workers and the sample is determined as many as 154 respondents. the sampling technique used is proportional random sampling. Data analysis was carried out with the Partial Least Square (PLS) approach using the SmartPLS 4.0 application. The results showed that work involvement and organizational culture had a positive and significant effect on the performance of extension workers. In addition, cohesiveness was shown to partially mediate the effect of work engagement on extension worker performance, which indicates that cooperation and solidarity between teams play an important role in strengthening the impact of individual engagement on performance. Finally, cohesiveness mediates the effect of organizational culture on the performance of agricultural extension workers. This study concludes that improving the performance of agricultural extension workers requires a comprehensive strategy, not only through increasing individual engagement, but also through strengthening the work culture and cohesiveness of a supportive team.